Association Colloids Formed by Multiple Surface Active Minor Components and Their Effect on Lipid Oxidation in Bulk Oil. (17th September 2014) - Kittipongpittaya, Ketinun; Panya, Atikorn; Cui, Leqi; McClements, David Julian; Decker, Eric Andrew
Abstract: Association colloids formed by surface active minor components play an important role in the oxidative stability of bulk oils. To imitate the formation of nanostructures in refined oils, multiple surface active minor components including phospholipids, free fatty acids, diacylglycerols and sterols were added to stripped corn oil. The critical micelle concentration (CMC) of the mixed components was determined. The impact of mixed minor components at below and above their CMC on oxidative stability of bulk oil and on antioxidant activity of α‐tocopherol and Trolox was investigated. The CMC of the mixed surface active components in bulk oil was 20 µmol/kg oil in the presence of 383 ± 2 ppm of water. 1, 2‐Dioleoyl‐ sn ‐glycero‐3‐phosphocholine (DOPC) played an important role on the formation of association colloids since it was the most important component in forming the association colloids as confirmed by CMC and fluorescence probe studies. The association colloids formed by the mixed components showed prooxidative activity in bulk oil as determined by monitoring the formation of lipid hydroperoxide and hexanal. The activity of α‐tocopherol or Trolox was not changed by mixed components association colloids. These results suggest that association colloids both physically and chemically impacted the oxidative stability and activity of antioxidants in bulk oil.